Improvement and Roles of the USU Community Service Team in Educating Halal Certification to the Giat Maju Farmer Group in Parbuluan Village VI Dairi - Hilman, Adrian (Talenta Publisher Universitas Sumatera Utara, 2024)
Currently, the need for halal products has increased rapidly. Halal food has become a profitable business with the largest market share, especially in Indonesia. To improve the quality of the coffee products of the Giat Maju farmer group in Parbuluan VI Dairi Village, the USU community service team is given to educate about halal certification and how to register it. The product certification can expand the market reach of product buyers, and buyers will feel safe and comfortable. Thus, this can increase sales of partner coffee products. Some of the activities carried out by the community service team are identify the problem, socialization and education, document creation and collection, registration and completion of facilities and infrastructure, and assistance for registration of LPPOM MUI halal certification. From the socialization, partners strongly desire to obtain halal product certification by building new production houses, participating in halal certification webinars, and preparing all required documents for registration.